COMPARATIVE ANALYSIS OF TYPOLOGY IN UZBEK AND ENGLISH FOLK PROVERBS - Nigora Tojiboyeva Shokirjon qizi (Research Focus International Scientific Journal, 2024)
This study presents a comparative analysis of the typology found in Uzbek and English folk proverbs. A corpus of proverbs from both cultures was analyzed for syntactic structures, semantic components, and cultural connotations. Results highlight significant typological variations, rooted in historical, cultural, and linguistic influences. The discussion delves into the impact of communal values, individualistic ethos, and societal structures on the development of folk proverbs, fostering a deeper understanding of cross-cultural communication.